2005
DOI: 10.1093/jac/dki410
|View full text |Cite
|
Sign up to set email alerts
|

Caspofungin treatment in severely ill, immunocompromised patients: a case-documentation study of 118 patients

Abstract: This open case study of severely ill patients with invasive fungal infections demonstrates both excellent efficacy and very low toxicity of caspofungin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 18 publications
2
27
0
Order By: Relevance
“…Both surveys show that the common species-C. albicans, C. glabrata, and C. tropicalis-are highly susceptible to all three agents, whereas elevated MICs (1 g/ml to 4 g/ml) are seen for C. parapsilosis and C. guilliermondii. The available clinical data indicate that these species respond similarly to treatment with each of these agents (29,41,87,114,119,163,184,219,274); however, it should be noted that persistent fungemia with C. parapsilosis has been observed in the face of caspofungin therapy (163). In light of these findings, it is also important to know that caspofungin has been shown to lack fungicidal activity against C. parapsilosis (and C. guilliermondii) (17a).…”
Section: Trends In Antifungal Susceptibility In Relation To Time Geomentioning
confidence: 99%
See 2 more Smart Citations
“…Both surveys show that the common species-C. albicans, C. glabrata, and C. tropicalis-are highly susceptible to all three agents, whereas elevated MICs (1 g/ml to 4 g/ml) are seen for C. parapsilosis and C. guilliermondii. The available clinical data indicate that these species respond similarly to treatment with each of these agents (29,41,87,114,119,163,184,219,274); however, it should be noted that persistent fungemia with C. parapsilosis has been observed in the face of caspofungin therapy (163). In light of these findings, it is also important to know that caspofungin has been shown to lack fungicidal activity against C. parapsilosis (and C. guilliermondii) (17a).…”
Section: Trends In Antifungal Susceptibility In Relation To Time Geomentioning
confidence: 99%
“…As the first of the echinocandins to be approved for the treatment of IC, caspofungin has been used extensively for the treatment of all forms of serious candidal infections over the past 4 years (87,114,134,171,261). Thus far, clinical experience with caspofungin and IC has been good (41,87,114,163,171).…”
Section: Trends In Antifungal Susceptibility In Relation To Time Geomentioning
confidence: 99%
See 1 more Smart Citation
“…Outcome is better if patients have well-controlled underlying disease and granulocyte count greater than 1000 [13] Amphotericin B, fluconazole, itraconazole and variconazole have been used with success in several cases of pulmonary or invasive aspergillosis [2] with different effective rates. In 2006, Glasmacher et al reported the efficacy and safety of Caspofungin (CF) in a large unselected population of patients with fungal infections in Germany [14]. CF, which is the first-in-echinocandin class, is an antifungal drug with a broad spectrum of activity and excellent tolerbility.…”
Section: Discussionmentioning
confidence: 99%
“…The alternatives include high-dose liposomal amphotericin B, echinocandins, or the newer azole drugs, such as itraconazole or voriconazole [11] . Caspofungin has been shown to be efficacious during empirical antifungal therapy for neutropenic patients or severely ill patients with refractory invasive Aspergillus infections and invasive candidiasis [12] .…”
Section: Discussionmentioning
confidence: 99%